THE IMPLEMENTATION OF CHARACTER EDUCATION TO SHAPE THE STUDENTS' LEARNING MOTIVATION TO LEARN ENGLISH - Vovi Enizah; Djunaidi Djunaidi; Marleni Marleni (Universitas PGRI Palembang, 2024)
Implementing character education in elementary schools has become mandatory. Because apart from the rules, it is also the obligation of educational institutions to educate their students. This article aims to explore how character education can be implemented effectively in the context of forming students' learning motivation in English lessons. English is a foreign language that has a central role in the world of education. In line with current curriculum demands, English language learning in schools is expected to not only focus on increasing students' communication competence in English, but also have a positive impact in instilling and shaping students' character and fostering motivation in learning. The research method used is field research, qualitative approach, primary and secondary data sources, data collection techniques using observation, interviews, documentation, data analysis techniques include data reduction, data presentation, and conclusion drawing (verification). The research results obtained at SD Negeri 231 Palembang as an implementation of character education include: students are more enthusiastic and enthusiastic when learning English. In its implementation there are inhibiting factors including limited time and inadequate facilities